The first finding of a natural infection of Cryptosporidium muris in a cat - Pavlasek, Ivan; Ryan, Una (Veterinary parasitology, 2007)
Little is known about the species of Cryptosporidium infecting cats. The limited number of genetic studies conducted to date, have all identified C. felis as the species of Cryptosporidium in cats. We report a morphological and genetic description of a natural C. muris infection in a cat. Oocysts were viable and were successfully transmitted to laboratory mice. Further studies are required to determine the range and prevalence of Cryptosporidium species infecting cats.
Keywords: Animals; Base Sequence; Cats; kryptosporidióza; Cryptosporidiosis; RNA, Ribosomal, 18S; nemoci koček; zvířata; feces; Feces; Cat Diseases; kočky; RNA ribozomální 18S; Cryptosporidium; sekvence nukleotidů